Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

Exploring intergenerational differences in consumer acceptance of insects-fed farmed fish - M.T. Trentinaglia; M. Adler; M. Peri; L. Panzone; L. Baldi (Food Quality and Preference, 2024)

Marine turtles as bio-indicators of plastic pollution in the eastern Mediterranean - Emily M. Duncan; Hasan Deniz Akbora; Patrizia Baldi; Damla Beton; Annette C. Broderick; Burak Ali Cicek; Charlotte Crowe-Harland; Sophie Davey; Tess DeSerisy; Wayne J. Fuller; Julia C. Haywood; Yu Jou Hsieh; et al. (Marine Pollution Bulletin, 2024)

Pesticide exposure in greenspaces: Comparing field measurement of dermal contamination with values predicted by registration models - L. de Graaf; M. Bresson; M. Boulanger; M. Bureau; Y. Lecluse; P. Lebailly; I. Baldi (Science of The Total Environment, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Improved process conditions for increasing expression of MHC class II protein from a stable Drosophila S2 cell line - Xiao Shen; Danijel Dojcinovic; Lucia Baldi; David L. Hacker; Immanuel F. Luescher; Florian M. Wurm (Biotechnology Letters, 2018)

Nutritional evaluation of former food products (ex-food) intended for pig nutrition - C. Giromini; M. Ottoboni; M. Tretola; D. Marchis; D. Gottardo; V. Caprarulo; A. Baldi; L. Pinotti (Food Additives & Contaminants: Part A, 2017)

An empirical study on consumer acceptance of farmed fish fed on insect meals: the Italian case - T. Mancuso; L. Baldi; L. Gasco (Aquaculture International, 2016)

Genetic association between temperament and sexual precocity indicator traits in Nellore cattle - T. S. Valente; A. C. Sant’Anna; F. Baldi; L. G. Albuquerque; Mateus J. R. Paranhos da Costa (Journal of Applied Genetics, 2015)

Genetic parameters and investigation of genotype × environment interactions in Nellore × Hereford crossbred for resistance to cattle ticks in different regions of Brazil - D. R. Ayres; R. J. Pereira; A. A. Boligon; F. Baldi; V. M. Roso; L. G. Albuquerque (Journal of Applied Genetics, 2015)

Computer image analysis: an additional tool for the identification of processed poultry and mammal protein containing bones - L. Pinotti; T. Fearn; S. Gulalp; A. Campagnoli; M. Ottoboni; A. Baldi; F. Cheli; G. Savoini; V. Dell’Orto (Food Additives & Contaminants: Part A, 2013)

Reduced glutamine concentration improves protein production in growth-arrested CHO-DG44 and HEK-293E cells - Yashas Rajendra; Divor Kiseljak; Lucia Baldi; David L. Hacker; Florian M. Wurm (Biotechnology Letters, 2012)

TubeSpin bioreactor 50 for the high-density cultivation of Sf-9 insect cells in suspension - Qiuling Xie; Patrik O. Michel; Lucia Baldi; David L. Hacker; Xiaowei Zhang; Florian M. Wurm (Biotechnology Letters, 2011)

Hyperosmolarity enhances transient recombinant protein yield in Chinese hamster ovary cells - Xiaowei Zhang; Isabel Fernandez Garcia; Lucia Baldi; David L. Hacker; Florian M. Wurm (Biotechnology Letters, 2010)

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)

Evaluation the of PL-PG-PA system in relation to quality of bovine milk - L. Rossi; F. Galante; E. Fusi; M. Luini; V. Dell’Orto; A. Baldi (Veterinary Research Communications, 2009)

Evaluation of the damage induced by ochratoxin A and the protective role of α-tocopherol in cultured bovine mammary epithelial cells - E. Fusi; R. Rebucci; C. Pecorini; L. Rossi; F. D’Ambrosio; A. Baldi (Veterinary Research Communications, 2008)

Influence of the sample collection method on salivary interleukin–6 levels in resting and post-exercise conditions - M. A. Minetto; M. Gazzoni; F. Lanfranco; M. Baldi; L. Saba; R. Pedrola; P. V. Komi; A. Rainoldi (European Journal of Applied Physiology, 2007)

Effects of Rumen-protected Choline Supplementation in Periparturient Dairy Goats - F. D’Ambrosio; A. Campagnoli; F. Susca; E. Fusi; R. Rebucci; A. Agazzi; L. Pinotti; A. Baldi (Veterinary Research Communications, 2007)

Recombinant protein production by large-scale transient gene expression in mammalian cells: state of the art and future perspectives - Lucia Baldi; David L. Hacker; Myriam Adam; Florian M. Wurm (Biotechnology Letters, 2007)

Cyclo-oxygenase-2 (COX-2) inhibition reduces apoptosis in acute myocardial infarction - A. Abbate; F. Limana; M. C. Capogrossi; D. Santini; G. G. L. Biondi-Zoccai; S. Scarpa; A. Germani; S. Straino; A. Severino; F. Vasaturo; M. Campioni; G. Liuzzo; et al. (Apoptosis, 2006)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Antigenic Recombinant Proteins Expressed in Tobacco Seeds as a Model for Edible Vaccines Against Swine Oedema - L. Rossi; A. Baldi; V. Dell'Orto; C. Fogher (Veterinary Research Communications, 2003)

Milk Choline, α-Tocopherol and Neutrophil Chemotaxis in the Periparturient Dairy Cow - L. Pinotti; R. Rebucci; E. Fusi; L. Rossi; A. Baldi (Veterinary Research Communications, 2003)

Nackt ( nkt ), a new hair loss mutation of the mouse with associated CD4 deficiency - F. Benavides; Mirta Giordano; Laurence Fiette; Ana Lcia Bueno Brunialti; N. Martin Palenzuela; Silvia Vanzulli; Pablo Baldi; Reiner Schmidt; Christiane Dosne Pasqualini; J.-L. Gunet (Immunogenetics, 1999)